Increase in urinary growth hormone excretion in puberty. Issue 11 (November 1990) - Price, D A; Addison, G M; Herbert, E D
Abstract : During the pubertal years the overnight urinary excretion rate of growth hormone (hGHu) increases to three to four times the prepubertal rate, reaching a peak in girls at 13 years and in boys at 15 years. After puberty the mean rate of overnight hGHu is twice that before puberty.